Characteristics of regional industry‐specific employment growth rates' distributions. (18th February 2013) - Duschl, Matthias; Brenner, Thomas
Abstract Regional growth dynamics deviate from a normal distribution. Using industry‐specific employment data for German regions, we find that the asymmetric exponential power distribution best accounts for the high frequency of extreme positive and especially negative growth events. This research confirms previous studies on growth rates of firms, industries and countries and fills the research gap at the level of regions. Furthermore, we show that even in the case of prolonged time lags, regional industry‐specific employment growth rates are far from being normally distributed, move towards a Laplacian shape and that knowledge intensive industries increase the regional economies' risk of being affected by extreme events of growth and decline.